2012
DOI: 10.1007/s11065-012-9222-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cannabis on Neurocognitive Functioning: Recent Advances, Neurodevelopmental Influences, and Sex Differences

Abstract: Decades of research have examined the effects of cannabis on neurocognition. Recent advances in this field provide us with a better understanding of how cannabis use influences neurocognition both acutely (during intoxication) and non-acutely (after acute effects subside). Evidence of problems with episodic memory is one of the most consistent findings reported; however, several other neurocognitive domains appear to be adversely affected by cannabis use under various conditions. There is significant variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
243
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(260 citation statements)
references
References 218 publications
(376 reference statements)
13
243
0
4
Order By: Relevance
“…Furthermore, much like smoking tobacco cigarettes while driving (Stevens & Minton, 2001), handling marijuana materials while driving detracts from attention to the road and surroundings. Coupled with established impairments in attention and concentration during marijuana intoxication (Crane et al, 2013;Ramaekers et al, 2009), SMWD ultimately places the driver, passengers, and others at risk.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…Furthermore, much like smoking tobacco cigarettes while driving (Stevens & Minton, 2001), handling marijuana materials while driving detracts from attention to the road and surroundings. Coupled with established impairments in attention and concentration during marijuana intoxication (Crane et al, 2013;Ramaekers et al, 2009), SMWD ultimately places the driver, passengers, and others at risk.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…5,6 Concerns have been raised over this rising potency of cannabis, given that higher levels of THC may induce anxiety and psychosis, and because acute cannabis use is associated with cognitive impairments in the domains of learning, memory, reasoning and attention. 7,8 Comparatively, the role of cannabinoid signalling in decision-related executive processes is unexplored. Crucial decisions in life require evaluating the costs associated with different options in light of the potential benefits obtained by those choices.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported marijuana-associated impairments in frontal function, most notably during tasks that require executive control, inhibition, and decision making (for review, see Crane et al, 2013;Crean et al, 2011). Further, several investigations have specifically examined the role of age at marijuana onset, with results suggesting that earlier age at marijuana onset is related to impairment on measures of visual scanning (Ehrenreich et al, 1999), verbal IQ (Pope et al, 2003;Solowij et al, 2011), and executive function (Battisti et al, 2010;Fontes et al, 2011;Gruber et al, 2012b).…”
mentioning
confidence: 99%